The Arm's Length Principle in Mitigating Tax Avoidance: A Systematic Literature Review - I Kadek Agus Ardika; Putu Novia Hapsari Ardianti; Cokorda Istri Agung Evita Nindia Putri (International Journal of Applied Business and International Management, 2025)
This study examines the effectiveness of Transfer Pricing Documentation (TP Doc) in supporting the Arm’s Length Principle (ALP) to reduce tax avoidance through related-party transactions (RPTs), especially involving tax haven jurisdictions. Using a Systematic Literature Review (SLR) approach, 15 relevant studies published between 2015 and 2024 were analyzed. The literature was selected based on keywords such as “Profit Shifting,” “Tax Haven,” “Related Party Transaction,” “Tax Avoidance,” and “Transfer Pricing.” The findings indicate that TP Doc contributes significantly to enhancing transparency and providing accurate information that enables tax authorities to evaluate whether intercompany transactions reflect fair market values. However, its implementation faces several challenges, including limited access to reliable data, inconsistencies in international standards, low compliance levels, and exploitable loopholes. Additionally, multinational enterprises (MNEs) frequently use RPTs to shift profits to low-tax jurisdictions, reducing their overall tax obligations. The study highlights the need to strengthen regulations, enhance tax authority enforcement, and promote international cooperation to ensure TP Doc effectively supports Indonesia’s tax reform and compliance efforts.